2011
DOI: 10.1177/1468018111421287
|View full text |Cite
|
Sign up to set email alerts
|

Social policy development and global financial crisis in the open economies of Botswana and Mauritius

Abstract: The manner in which open economies in a globalized world shape social policy development is highly disputed, as is the impact of the current financial crisis on social policy. One argument is that globalization and economic austerity force social policy dismantling. Alternatively, it is proposed that open economies -facing greater volatility, especially during crisis -push for greater social protection. Using the examples of Botswana and Mauritius, two open middle-income countries, this article suggests that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Social assistance programmes were introduced, in the first instance, to tide peasants through periods of drought, and later to protect those specific groups (the elderly, orphans, 'destitutes') who fell through the cracks of agrarian society. Ulriksen (2011Ulriksen ( , 2012 underestimates the extent of the welfare state in Botswana, by neglecting drought relief and peasant-support programmes. Under the BDP, a welfare state was built, but it was a conservative one.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social assistance programmes were introduced, in the first instance, to tide peasants through periods of drought, and later to protect those specific groups (the elderly, orphans, 'destitutes') who fell through the cracks of agrarian society. Ulriksen (2011Ulriksen ( , 2012 underestimates the extent of the welfare state in Botswana, by neglecting drought relief and peasant-support programmes. Under the BDP, a welfare state was built, but it was a conservative one.…”
Section: Resultsmentioning
confidence: 99%
“…Under the BDP, a welfare state was built, but it was a conservative one. Ulriksen (2011Ulriksen ( , 2012 also exaggerates the reach of 'neo-liberalism' in Botswana in the 2000s. The government did reintroduce school fees, but then exempted the poor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this, Skocpol and Amenta add previously established social policies' ability to define the public agenda and patterns of group conflict, thus influencing subsequent policy (ibidem: 149). Reinforcing the argument, recent analyses show that the impact of globalization and economic crisis depend on the characteristics of previously established Welfare States and organized systems (Ulriksen, 2011).…”
Section: Legacymentioning
confidence: 89%
“…Several authors have shown, on the one hand, that there is a significant correlation between spending on social protection in a country and the death rate (Esu & Inyang, ). On the other hand, the severe economic crisis that affected Finland at the beginning of the nineties had no negative effect on health or on inequalities in health because of the strength of this country's Welfare State (Ulriksen, ). These studies show that the harmful impact on health is related to the level of protection of citizens.…”
Section: Ethical Recommendations Before Austerity Policies In Healthcarementioning
confidence: 99%